An Assessment of Stress Patterns among Cadets of Nigerian Defence Academy, Kaduna, Nigeria - Garba, Jummai; Okorie, Agnes; Aigboje, Hauwa (NIU Journal of Social Sciences; Vol 8 No 2 (2022): NIU Journal of Social Sciences, Vol. 8 No. 2, June 2022DO - 10.58709/niujss.v8i2.1463, 2022)
Stress is a normal and natural response of the body to a stressful situation. People respond to harmful situations differently. The way we tolerate exposure to stress varies from person to person. Our perception of any given circumstance determines our emotional and psychological outcome. Some people are resilient to stress while others are not, some are more stressed than others. The study is to examine the patterns of stress among cadets of Nigerian Defence Academy, Kaduna. Quantitative survey design was used for the research where 225 cadets, 181 males and 44 females were randomly sampled from faculties of Arts and Sciences. Stress Symptom Checklist (SSCL) was used as instrument to gather data. Frequencies and percentages were used to describe the data while independent t test was used to analyzed the data. Findings revealed that significant difference exits in the patterns of stress experienced by cadets, more cadets experience psychological stress than physical stress. On the hand the result indicated no significance difference in the stress patterns experience by art or science cadets and by male or female cadets. This implies that cadets have different patterns of experiencing stress but the way they experience stress is not different whether they study arts or science subjects or whether they are males or females. Naturally it is expected that more cadets should experience physical stress but it turned the other way. Thus, this suggests that more attention should be focused in managing psychological stress than physical stress among the cadets. Keywords: Stress, Stress Patterns, Cadets, Nigerian Defence Academy